ANSWER
True
Step-by-step explanation
The given trigonometric equation is
![\tan^(2) (x) = (1 - \cos(2x) )/(1 + \cos(2x) )](https://img.qammunity.org/2019/formulas/mathematics/college/vk3dwy5w1u5aut7pr7x21c2ctdykvjpe1u.png)
Recall the double angle identity:
![\cos(2x) = \cos^(2) x - \sin^(2)x](https://img.qammunity.org/2019/formulas/mathematics/college/7m4ouvf0etdetflq9ijh4rxjv146yttktp.png)
We apply this identity to obtain:
![\tan^(2) (x) = (1 - (\cos^(2) x - \sin^(2)x) )/(1 + (\cos^(2) x - \sin^(2)x) )](https://img.qammunity.org/2019/formulas/mathematics/college/vvlhk489bwbs2a8sj3iqf6wjek8ob0bubt.png)
We maintain the LHS and simplify the RHS to see whether they are equal.
Expand the parenthesis
![\tan^(2) (x) = (1 - \cos^(2) x + \sin^(2)x )/(1 + \cos^(2) x - \sin^(2)x)](https://img.qammunity.org/2019/formulas/mathematics/college/pa8o5ync3z4w2dauwzrv8is4s4w1aaf9pn.png)
![\implies\tan^(2) (x) = (1 - \cos^(2) x + \sin^(2)x )/(1 - \sin^(2)x + \cos^(2) x )](https://img.qammunity.org/2019/formulas/mathematics/college/xihyvrug1a8r7yx18hqvtxhe8ng0c8to08.png)
Recall that:
![1 - \sin^(2)x = \cos^(2)x](https://img.qammunity.org/2019/formulas/mathematics/college/8m52y1dsbfly62vz35l5k90ku2a9f0fi7x.png)
![1 - \cos^(2)x = \sin^(2)x](https://img.qammunity.org/2019/formulas/mathematics/college/2x4m5f7x3q45pel6wnrheumxk7q2jeodx4.png)
We apply these identities to get:
![\implies\tan^(2) (x) = (\sin^(2)x + \sin^(2)x )/(\cos^(2) x + \cos^(2) x )](https://img.qammunity.org/2019/formulas/mathematics/college/hlhsut7o01i10iyd7ba669la1gkuvxk4qf.png)
![\implies\tan^(2) (x) = (2\sin^(2)x )/( 2\cos^(2) x )](https://img.qammunity.org/2019/formulas/mathematics/college/27kmlg20u6u7p2f5xv39r0cn94k5edyyqh.png)
![\implies\tan^(2) (x) = (\sin^(2)x )/( \cos^(2) x )](https://img.qammunity.org/2019/formulas/mathematics/college/qx36v65dqojamnmy4an5vk5gcyf0n9rb3c.png)
![\implies \tan^(2) (x) =( (\sin x )/( \cos x ))^(2)](https://img.qammunity.org/2019/formulas/mathematics/college/fb3tn041jm9t23aqvbpxpeey8ytmpscgls.png)
Also
![(\sin x )/( \cos x ) = \tan(x)](https://img.qammunity.org/2019/formulas/mathematics/college/w2hoqrai9u6fux4os87ko9vmxpgsnwhuog.png)
![\implies \tan^(2) (x) =( \tan x )^(2)](https://img.qammunity.org/2019/formulas/mathematics/college/jj8zz8390y5a4e7nnntb78ud9s9087jgkw.png)
![\implies \tan^(2) (x) =\tan^(2) (x)](https://img.qammunity.org/2019/formulas/mathematics/college/q8dylqz9r6q5q01l6aenyqlvi0wtn54yal.png)
Therefore the correct answer is True